Pengaruh Kemiskinan dan Pengangguran terhadap Indeks Pembangunan Manusia di Lampung 2021-2023 - Bibit Waluyo; Cahyani Dwi Era Wati; Desta Ayu Aristianti; Farhan Trisna Maulana; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The human development index is a way to assess the extent of the welfare of society in an area. Human development in Lampung Province is ranked lowest among other provinces on the island of Sumatra with a percentage of 70.45% in 2022. Departing from the geographical context of Lampung Province which is a vital route for economic activity between the islands of Java and Sumatra, this province has the potential to become a center distribution of goods and services at the national level. It should be able to increase employment and income in Lampung Province. So, it can reduce poverty and reduce unemployment. However, in reality, Lampung Province is still far behind other provinces on the island of Sumatra. The formulation of the problem in this research is how poverty and unemployment influence the human development index in Lampung Province. This research uses a quantitative type of research with a descriptive approach using panel data with a fixed effect model approach. The population in this research is data from the Human Development Index contained in the Central Statistics Agency of Lampung Province. According to the research results, X1 has a significant negative effect, X2 has no significant effect. The results of statistical tests state that the value of Prob. (F-statistic) is 0.000000. This means 0.000000<0.05, so it can be concluded that the independent variable (X) has a significant effect on the dependent variable (Y) simultaneously (simultaneously). Based on the results of the statistical tests carried out, an R-squared value of 0.984344 was obtained. It can be concluded that the independent variable has an influence on the dependent variable of 98%, while 2% is influenced by other variables outside the model.